The Impact of Hybrid Quantum Learning Methods on Arabic Language Acquisition Among Students of Islamic Boarding School in Indonesia (Journal of Arabic Language Learning and Teaching (JALLT), 2024)
The study explores Hybrid Quantum Learning in Arabic language education amid COVID-19, employing a quantitative approach with descriptive research methods. Data collection includes observation, interviews, tests, and questionnaires, analyzed through descriptive techniques and hypothesis testing. Experimental and control groups assess Hybrid Quantum-Classical Learning's efficacy, showing a 63.34% average difference in the former and 62.95% in the latter, indicating somewhat effective outcomes. Initially lacking, student engagement improved with model implementation. Further examination, supported by Likert scale responses, reveals an 87.33% satisfaction rate among students, highlighting the effectiveness of teaching auditory, visual, and kinesthetic skills in Arabic language education, particularly during the pandemic at Hasanka Islamic Boarding School in Indonesia.